(untitled) (Research, Society and Development, 2021)
The Tabebuia genus is one of the largest genera of the Bignoniaceae family, comprising more than 100 species. One of its main representatives is the ipê tree, which is popularly known for their ornamental and logging potential. However, parts of the tree, such as the stem, leaves and flowers, are used in traditional medicine for anti-bacterial, anti-inflammatory (rhinitis, sinusitis, tonsillitis and pharyngitis), anti-ulcerogenic, antiviral, antineoplastic, antimalarial and immunomodulatory purposes. The objective of the present study was to collate articles on the cicatrizing and therapeutic properties of species belonging to the Tabebuia spp genus.